DEEP LEARNING-BASED CYBER PEDAGOGY MODEL TO IMPROVE 4C SKILLS (CRITICAL THINKING, COLLABORATION, CREATIVITY, AND COMMUNICATION) - Maula, Putrinda Inayatul; Patmanthara, Syaad; Masyfa, Faiz Hilmawan; Sari, Heni Vidia; Hanifah, Nida; Rachman, Tegar Fatur (STKIP PGRI Tulungagung, 2026)
The need to strengthen 4C skills (critical thinking, collaboration, creativity, and communication) in vocational high school (SMK) students in the digital era is becoming increasingly urgent. However, the integration of Deep Learning (DL) in the cyber pedagogy framework to address these challenges is still limited. This study aims to develop a deep learning-based cyber pedagogy model to improve the 4C skills of SMK students. The approach used is Research and Development (RD) with the prototype method through the stages of needs analysis, conceptual model development, validation, and dissemination. Preliminary analysis results show varying 4C skill profiles, with collaboration being the main strength (mean=3.13) followed by creativity (mean=3.08), while critical thinking remains the biggest challenge (mean=2.99). In addition, communication has the highest standard deviation (0.71), indicating a competency gap among students. The proposed model integrates DL to analyze student activities, such as written arguments, discussion interactions, and project originality, to generate adaptive and real-time feedback. Factors supporting the implementation of the model include the readiness of digital infrastructure, teachers' mastery of TPACK, and progressive institutional policies towards learning innovation. Conversely, the main challenges include limitations in AI literacy, resistance to pedagogical change, and issues of ethics and data security. This model offers a holistic approach that bridges pedagogy and advanced technology, creating personalized, collaborative, and data-driven learning. Thus, this research makes a strategic contribution to preparing highly competitive vocational school graduates who are relevant to the needs of the future digital industry.